Potrjena gnezditev sirijskega detla Dendrocopos syriacus v Sloveniji - Bačani, Smiljan (Acrocephalus, 1998)
The confirmed breeding of the Syrian Woodpecker in Slovenia is described. A pair of these birds bred in May 1997 at Malečnik near Maribor, with their nest hole situated in a white poplar Populus alba some 5 metres from the ground. This species had been observed for the first time in our country in 1974, while in 1978 a female of the Syrian Woodpecker was found to breed with a male of the Great Spotted Woodpecker. All the observations were made, with the exception of this crossbreeding, in the eastern part of Slovenia...
Keywords: bird; ptice; Dendrocopos syriacus; ornitologija; Slovenia; Slovenija